IMPLEMENTASI BINA DIRI DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN PERILAKU ADAPTIF SISWA (Studi pada Siswa Kelas VIII C SLB YPPABK Ngawi) - binti sholekah, anisah (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
Self-help learning in class VIII C of YPPABK Ngawi extraordinary school in practice still needs a lot of development based on complaints experienced by the teacher of class VIII C self-help subjects when learning self-help very often performs non-adaptive behavior when learning takes place students are difficult to control, often tantrum and hurt themselves, students are not focused when eye contact, students often spit, slam and grab friends' belongings, students often go to the bathroom and do not return to class when the lesson is still ongoing, students experience a decrease in response when communicating, students are less able to understand simple instructions such as sitting, standing and squatting, students often do not go to school when there are scheduled self-help lessons. This study aims to determine self-help in class VII C, find out the causes of students doing non-adaptive behavior, the application of self-help with modeling techniques and the improvement of students' adaptive behavior.The use of modeling techniques in self-help lessons is expected to make it easier for students to understand, practice the material provided and can improve existing adaptive behavior. The type of research used is qualitative which is descriptive qualitative with a case study model. The subject of this research is the teacher of self-help subjects in class VIII C of Sekolah Luar Biasa Ngawi. The data collection methods are observation, interview and documentation. The results of this study are the application of self-help with modeling techniques can improve the adaptive behavior of students in class VIII C of YPPABK Ngawi special school. This modeling technique makes it easier for students to understand, practice the material delivered by the teacher and improve students' adaptive behavior as seen from changes in students' behavior and attitudes in social interactions with all teachers and with their classmates, they never do non-adaptive behavior as before.